PAHs contamination in chosen samples taken from the Olecko region - Chrząścik, Ireneusz; Szymalska, Magdalena; Kluska, Mariusz (Studia Ecologiae et Bioethicae, 2007)
This paper presents the results of research conducted on some samples with soil and cabbage taken from the vicinity of Olecko town (Suwałki, Gołdapia, Ełk, Giżycko) and containing polycyclic aromatic hydrocarbons (PAHs) with 16 aromatic rings, the research is a continuation of a detailed monitoring of progressing pollution in the Olecko region, the samples were taken in August 2006 from the place situated 10 m from a road, this place was at the same time a cabbage plantation, the highest concentration of PAHs (750 pg/kg s. m.) was found in the sample taken close to the road from Olecko to Suwałki and in the sample with cabbage (313 pg/kg s. m.) taken near the road to Gołdapia. The lowest concentration of PAHs was stated in the samples taken in the vicinity of the road to Giżycko, the results don’t overpass the limits permitted in Poland but, unfortunately, are close to the upper limit of natural concentration defined by scientific literature.